Implementasi Nilai-Nilai Profil Pelajar Pancasila Dalam Penguatan Pendidikan Karakter - M. Hasan Asy’ari; Jauharul Ulum; Diajeng Arum Sari (Concept: Journal of Social Humanities and Education, 2025)
Character education in Indonesia is faced with various problems based on education only as a knowledge transfer activity, to overcome this, the Ministry of Education and Culture issued an independent curriculum to solve the problem. The purpose of this study is how the method applied by MI Sunan Kalijogo in habituating character education based on the Pancasila student profile. The method used in this research is descriptive qualitative, the data from this study were obtained from interviews, observation, documentation, and literature research which are then called primary and secondary data. Character education based on Pancasila learner profile applied by MI Sunan Kalijogo is congregational prayer activities, religious studies, and MTQ. The implication of this research is a form of strengthening P5 and reconstructing character education patterns for schools at the elementary school level that use an independent curriculum.